2017
DOI: 10.1175/jas-d-17-0043.1
|View full text |Cite
|
Sign up to set email alerts
|

Broadening of Cloud Droplet Spectra through Eddy Hopping: Turbulent Adiabatic Parcel Simulations

Abstract: This paper investigates spectral broadening of droplet size distributions through a mechanism referred to as the eddy hopping. The key idea, suggested a quarter century ago, is that droplets arriving at a given location within a turbulent cloud follow different trajectories and thus experience different growth histories and that this leads to a significant spectral broadening. In this study, the adiabatic parcel model with superdroplets is used to contrast droplet growth with and without turbulence. Turbulence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
98
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 33 publications
3
98
0
Order By: Relevance
“…Sardina et al (2015) also used a similar model to Lanotte et al (2009) but extended the simulation time to 20 min to be comparable to the formation time of rain revealed in real observations. They found that the variance of the droplet size distribution was mainly determined by the large-scale flow, i.e., the large-hopping effect suggested by Grabowski and Wang (2013) and studied by Grabowski and Abade (2017). Nevertheless, it should be noted that their conclusion was based on the simplified assumption that both the mean updraft speed and the mean supersaturation were zero.…”
Section: Introductionmentioning
confidence: 98%
“…Sardina et al (2015) also used a similar model to Lanotte et al (2009) but extended the simulation time to 20 min to be comparable to the formation time of rain revealed in real observations. They found that the variance of the droplet size distribution was mainly determined by the large-scale flow, i.e., the large-hopping effect suggested by Grabowski and Wang (2013) and studied by Grabowski and Abade (2017). Nevertheless, it should be noted that their conclusion was based on the simplified assumption that both the mean updraft speed and the mean supersaturation were zero.…”
Section: Introductionmentioning
confidence: 98%
“…Since fluctuations of temperature and the water mixing ratio are affected by turbulence, the supersaturation fluctuations are inevitably subjected to turbulence. Naturally, condensational growth due to supersaturation fluctuations became the focus (Sedunov, 1965;Kabanov and Mazin, 1970;Cooper, 1989;Srivastava, 1989;Korolev, 1995;Khvorostyanov and Curry, 1999;Sardina et al, 2015;Grabowski and Abade, 2017). The supersaturation fluctuations are particularly important for understanding the condensational growth of cloud droplets in stratiform clouds, where the updraft velocity of the parcel is almost zero (Hudson and Svensson, 1995;Korolev, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Various mechanisms such as entrainment with environmental air (Baker et al, 1980;Paluch & Knight, 1986;Telford & Chai, 1980;Warner, 1969), stochastic condensation (Khvorostyanov & Curry, 1999;Mazin & Smirnoff, 1969), and particle-turbulence interactions (Grabowski & Wang, 2013;Shaw, 2003) have been considered possible mechanisms to explain this broadening. Recently, numerical studies (Field et al, 2014;Grabowski & Abade, 2017;Paoli & Shariff, 2009;Sardina et al, 2015;Siewert et al, 2017) and observations of supersaturation variability (Ditas et al, 2012;Siebert & Shaw, 2017) have reignited the debate that stochastic condensation may play an important role in broadening of the size distribution. These build on the work by Cooper (1989) showing that stochastic condensation may still produce broadening despite the Journal of Geophysical Research: Atmospheres 10.1029/2018JD029033 limitations pointed out by Bartlett and Jonas (1972).…”
Section: Introductionmentioning
confidence: 99%